Analysis of Smartphone Purchasing Decisions Seen From The Lifestyle and Motivation of Consumer (Survey On Smartphone User In Eureunpalay Vilage, Cibalong District, Tasikmalaya Regency) - Rizky Adam Fauzi Fadilla; Rita Tri Yusnita; Barin Barlian (Journal of Indonesian Management, 2022)
The purpose of this study was to find out the influence of lifestyle and consumer motivation simultaneously and partially on survey purchase decisions on smartphone users in Eureunpalay Village, Cibalong Subdistrict, Tasikmalaya Regency. The research method used is a quantitative method with a causality survey approach. The sample in the study was 100 respondents. Data collection is done using questionnaires. The data analysis used is multiple regression analysis. The results of this study showed simultaneously the lifestyle and motivation of consumers have a significant influence on purchasing decisions. Partially lifestyle has a significant effect on purchasing decisions. Partially, consumer motivation has no significant effect on purchasing decisions.